INFLUENCE ANALYSIS OF MURABAHAH AND MUSYARAKAH RECEIVABLES WITH MODERATED REGRESSION ANALYSIS METHOD - Elfiswandi Elfiswandi; Muhammad Fikri Ramadhan; Fitri Indah Mayang Sari; Desi Rosalina (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to determine how influential Murabahah and Musyarakah receivables are on the profitability of Islamic banks with non-performing financing as a moderating variable. The population in this study are Islamic banks in Indonesia from 2015 to 2019. The sample for this study is 14 banks. This research methodology uses a saturated sample, namely where the entire population is sampled. data analysis method using panel data regression, EVIEWS. Based on the results of this study. Murabaha receivables have a negative effect on the profitability of Islamic banks. Musyarakah financing affects the Profitability of Islamic Banks. Murabahah Receivables and Musyarakah Financing jointly affect the Profitability of Islamic Banks. Non-performing financing weakens the relationship between Murabahah Receivables and Sharia Bank Profitability. Non performing financing strengthens the relationship between Musyarakah Financing and Sharia Bank Profitability